Rediscovering Phoenicians in their Homeland from the Perspective of Iron Age Coroplastic Art - Barbara Bolognani (Les Carnets de l’ACoSt)
The collective imagery of the Phoenicians is well known both within and outside of the academic world in large part because of the representations of daily life in their coroplastic art. Yet, there still is no comprehensive study of this genre of their material culture. In this brief communication, a new research project is presented that concerns a regional survey of Iron Age clay figurines from Phoenician sites in the eastern Mediterranean. The sites included in this research range beyond the borders traditionally ascribed to the Phoenicians, and cover the entire Syrian, Lebanese, and Israeli coasts. This research aims to illustrate the regional distribution of these figurines, including their production centers, as well as their types, uses, chronologies, and the meanings of this class of artefacts.